Sediment Profile Imaging: Laboratory Study Into the Sediment Smearing Effect of a Penetrating Plate - Moser, Annabell; Pheasant, Iain; MacPherson, William N.; Narayanaswamy, Bhavani E.; Sweetman, Andrew K. (Frontiers in Marine Science, 2021)
Sediment profiling imaging (SPI) is a versatile and widely used method to visually assess the quality of seafloor habitats (e.g., around fish farms and oil and gas rigs) and has been developed and used by both academics and consultancy companies over the last 50 years. Previous research has shown that inserting the flat viewport of an SPI camera into the sediment can have an impact on particle displacement pushing oxygenated surface sediments to deeper sediment depths and making anthropogenically-disturbed sediment appear healthier than they may actually be. To investigate the particle displacement that occurs when a flat plate is inserted into seafloor sediments, a testing device, termed the SPI purpose-built sediment chamber (SPI-PUSH) was designed and used in a series of experiments to quantify smearing where luminophores were used to demonstrate the extent of particle displacement caused by a flat plate being pushed into the sediment. Here, we show that the plate of the SPI-PUSH caused significant smearing, which varied with sediment type and the luminophore grain size. The mean particle smearing measured directly behind the inserted plate was 2.9 ± 1.5 cm for mud sediments with sand-like luminophores, 4.3 ± 2.5 cm for fine sand sediments with sand-like luminophores and 1.9 ± 1.1 cm for medium sand sediments with mud-like luminophores. When the mean depth of particle smearing was averaged over a larger sediment volume (11 cm3) next to the inserted plate, substantial differences were seen between the plate-insertion experiments and controls highlighting the potential extent of smearing artefacts that may be produced when a SPI camera penetrates the seafloor. This experimental data shows that future studies using the SPI camera, or any other periscope-like device (e.g., planar optodes) need to acknowledge that smearing may be significant. Furthermore, it highlights that a correction factor may need to be applied to these data (e.g., the depth of apparent redox potential discontinuity layer) to correctly interpret SPI camera images and better determine the effect of anthropogenic impacts on seafloor habitats.